2013
DOI: 10.1016/j.toxlet.2013.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Microglial disruption in young mice with early chronic lead exposure

Abstract: The mechanisms by which early chronic lead (Pb) exposure alter brain development have not been identified. We examined neuroimmune system effects in C57BL/6J mice with Pb exposure, including levels that may be common among children in lower socioeconomic income environments. Pups were exposed via dams’ drinking water from birth to post-natal day 28 to low, high or no Pb conditions. We compared gene expression of neuroinflammatory markers (study 1); and microglial mean cell body volume and mean cell body number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 47 publications
2
30
0
Order By: Relevance
“…Working memory is dependent on dentate gyrus (Aimone et al, 2011; Friedman and Goldman-Rakic, 1988; Xavier et al, 1999). Thus, this finding is consistent with the animal literature showing vulnerability of dentate gyrus to higher (Gilbert et al, 1996; Gilbert and Mack, 1998; Gilbert et al, 2005; Gilbert and Lasley, 2007) and lowest levels (Sobin et al, 2013) of lead exposure. Dentate gyrus is one of only three brain regions that supports neurogenesis throughout the lifespan and studies have also shown how higher levels of lead exposure alter neurogenesis (Gilbert et al, 2005).…”
Section: Discussionsupporting
confidence: 93%
“…Working memory is dependent on dentate gyrus (Aimone et al, 2011; Friedman and Goldman-Rakic, 1988; Xavier et al, 1999). Thus, this finding is consistent with the animal literature showing vulnerability of dentate gyrus to higher (Gilbert et al, 1996; Gilbert and Mack, 1998; Gilbert et al, 2005; Gilbert and Lasley, 2007) and lowest levels (Sobin et al, 2013) of lead exposure. Dentate gyrus is one of only three brain regions that supports neurogenesis throughout the lifespan and studies have also shown how higher levels of lead exposure alter neurogenesis (Gilbert et al, 2005).…”
Section: Discussionsupporting
confidence: 93%
“…Perhaps consistent with these findings, memory impairments have been found in children with BLLs similar to those of the low-dose mice in this study (<5 μg dl −1 ) (e.g., Min et al , 2007; Surkan et al , 2007). In addition, in brain studies of pre-adolescent C57BL/6J mice exposed to chronic low-level lead, abnormalities in hippocampus/dentate gyrus were identified (Sobin et al , 2013). The results of these studies should be interpreted cautiously.…”
Section: Discussionmentioning
confidence: 99%
“…Pb-induced oxidative stress or disruption of the pro-oxidant/antioxidant balance in blood and soft tissues is postulated to be the major mechanism of various tissue injuries (Ashry et al, 2010;Flora et al, 2003). Chronic exposure to Pb results in its accumulation, mainly in the liver, kidneys, and brain, as well as in other organs and tissues, where it causes many metabolic and histological changes, membrane damage, altered gene expression, and apoptosis (Kojima et al, 2002;Quintanilla-Vega et al, 2000;Sobin et al, 2013;Wang et al, 2013b). It causes oxidative stress by inducing the generation of reactive oxygen species (ROS), increasing the levels of lipid peroxidation (LPO) and thiobarbituric acid-reactive substances (TBARs), and inhibiting the activity of many antioxidant biomolecules (AlcarazContreras et al, 2011;Ashry et al, 2010).…”
Section: Introductionmentioning
confidence: 99%